Targeting clinical outcomes: Endovascular simulation improves diagnostic coronary angiography skills. Issue 3 (21st July 2015) - Schimmel, Daniel R.; Sweis, Ranya; Cohen, Elaine R.; Davidson, Charles; Wayne, Diane B.
Abstract : Objective: The purpose of this study is to determine the effects of simulation‐based medical education (SBME) on the skills required to perform coronary angiography in the cardiac catheterization laboratory. Background: Cardiovascular fellows commonly learn invasive procedures on patients. Because this approach is not standardized, it can result in inconsistent skill acquisition through exclusion of concepts and skills. Also, the learning curve varies between trainees yielding variability in skill acquisition. Therefore, coronary angiography skills are an excellent target for SBME in an environment in which direct patient care is not jeopardized. Methods: From January 2013 to June 2013, 14 cardiovascular fellows entering the cardiac catheterization laboratory at a tertiary care teaching hospital were tested on an endovascular simulator to assess baseline skills. All fellows subsequently underwent didactic teaching and preceptor‐lead training on the endovascular simulator. Topics included basic catheterization skills and a review of catheterization laboratory systems. Following training, all fellows underwent a post‐training assessment on the endovascular simulator. Paired t tests were used to compare items on the skills checklist and simulator defined variables. Results: Cardiovascular fellows scored significantly higher on a diagnostic coronary angiography skills checklist following SBME using an endovascular simulator. The mean pretest score was 66.6% (SD = 9.7%) compared to 86.0% (SD = 6.3%) following simulator training ( P < 0.001). Additional findings include significant reduction in procedure time and use of cine‐fluoroscopy at posttest. Conclusions: SBME significantly improved cardiovascular fellows' performance of simulated coronary angiography skills. Standardized simulation‐based education is a valuable adjunct to traditional clinical education for cardiovascular fellows. © 2015 Wiley Periodicals, Inc.